Knees Up Mother Earth - Rankin, Robert (London Gollancz, 2004)
"There's big trouble in Little Brentford. Property developers are planning to destroy Griffin Park, the borough's beloved football ground, and build executive homes on the site. Horror! Shock! Outrage! Something must be done." "The lads of The Flying Swan, Brentford's most celebrated drinking house, take up the challenge. Norman, keeper of the cornershop, has some ideas. He's recently discovered a Victorian computer which holds the long-lost secrets of the secret super-technology of a bygone age. And Archroy, Brentford's lone yachtsman and explorer, has just returned from his seventh voyage, bringing with him the fabled Golden Fleece." "Then there's Jim Pooley and John Omally, unemployed bachelors of this parish. And an aged, learned professor. And that Victorian time traveller who's recently materialised in Norman's kitchen." "Surely with all these stalwarts working for the cause, Brentford's football ground is as good as saved." "But this is Brentford, and ancient forces of evil - Old Testament terrors, Lovecraftian loathsomes and beasties from the bottomless pit, that sort of evil - are stirring. If the team make it through to the final, it's going to be a match that no one will forget." "What with the fate of mankind hanging upon the result and everything."--BOOK JACKET.
Keywords: Soccer stories -- Time travel